The Implementation of Article 43 of Law No. 41 of 2004 on Waqf in the Management of Productive Waqf Land Assets within the Muhammadiyah Organisation in Central Java - Achmad Arief Budiman; Islamiyati Islamiyati; Aisyah Ayu Musyafah; Bunga Jasmine Puji Hapsari (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2026)
The research was conducted due to a legal gap between Article 43 of the Waqf Law and its problematic implementation regarding institutional accountability and the professional capacity of the Nadir. The objective of the research is to analyse the implementation of Article 43 of Law No. 41 of 2004 on Waqf in the management practices of Muhammadiyah’s productive waqf land assets in Central Java, with regard to legal compliance and institutional accountability. The benefit is to optimise the Muhammadiyah Organisation’s waqf institution in the management in question. The research method employs a juridical-empirical approach within a socio-legal research framework, integrating normative legal analysis and empirical investigation. Data were obtained through observation, documentation, literature review, and interviews with representatives from the Ministry of Religious Affairs (KEMENAG), the Indonesian Waqf Board (BWI), the Indonesian Waqf Asset Management Agency (PPAIW), and the Nadir, as well as the management of the Muhammadiyah Central Java Regional Branch. Data analysis was qualitative, using content analysis. The research findings indicate that Muhammadiyah has implemented Article 43 of the Waqf Law regarding the management of waqf land, transitioning from a traditional model towards a semi-productive governance model supported by the strengthening of asset legality, institutional governance, the collection of cash waqf, and the development of a legal culture within social functions and public services. However, its implementation faces obstacles in the form of: disparities in managerial capacity, a low orientation towards productive investment, and an administrative accountability system that is not yet optimal. In conclusion, the Muhammadiyah organisation in Central Java has implemented the management of semi-productive waqf land; however, there is still a need to strengthen the legal status of waqf land assets and to optimise strategies for the management of productive waqf land based on community needs.